A STUDY COMPARING THE ANORECTIC ACTIVITY OF HOT AND COLD AQUEOUS EXTRACTS OF DOLICHOS BIFLORUS LINN. SEEDS IN FREELY FEEDING RATS - Shanmugapriya, S.; Senthurselvi, R; Bhuvaneswari, K. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The aim of the study was to evaluate the anorectic activity of hot (pre-cooked under pressure) and cold (soaked overnight) aqueous extracts of the seeds of D. biflorus in freely feeding Wistar albino rat model. Methods: Hot extract at a dose of 4 % w/v was given to the group 1 and cold extract at a dose of 4 % w/v was given to group 2 while group 3 was kept as the control group. Food intake and analysis of behavioral satiety sequence (BSS) was assessed after 4 w of extract administration whereas body weight was recorded both before and after treatment. Results: Cold extract group showed significant anorectic activity (p<0.05) but not the hot extract group. The cold extract group, unlike the hot extract group also exhibited an acceleration of the BSS indicating that the anorectic activity is primary. Conclusion: The study has thus brought out the potential appetite suppressant activity of the cold extract of D. biflorus seeds. Keywords: Dolichos biflorus, Anorectic, Behavioral satiety sequence, Food intake